2024
DOI: 10.1021/acsaom.3c00371
|View full text |Cite
|
Sign up to set email alerts
|

Stable Room-Temperature Phosphorescence from MXene-Derived Carbon Dots: Ultralong Afterglow Emission without an External Matrix

Bramhaiah Kommula,
Vinay Kumar Sriramadasu,
Srayee Mandal
et al.

Abstract: Herein, we synthesized highly defined carbon dots (CDs) from two-dimensional delaminated MXene through a solution-based acid etching method. The as-synthesized CDs show blue fluorescence emission in the solution phase upon neutralization with excess alkali. However, after solidification, the solid powder of CDs shows strong bright green room-temperature phosphorescence/afterglow emission for up to 5 s without using any further external matrix. The fundamental photophysical properties of the CDs are further cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…In addition, medium-intense peaks in CD 1 and CD 4 and more intense peaks in CD 2 and CD 3 are present at ∼1720 cm –1 due to carbonyl functional groups. A prominent peak corresponding to the −CC– bonds is observed in the 1620–1650 cm –1 region. ,,, In addition, in all samples, asymmetric and symmetric stretchings of −SO 3 groups are present at ∼1150 and ∼1017 cm –1 , respectively, originating from an H 2 SO 4 attack on the polymer backbone, and another peak at ∼860 cm –1 corresponds to the C–C ring and −CH 2 deformations. ,,, Notably, an additional peak (∼1265 and ∼730 cm –1 in CD 2 ) corresponds to the N–O stretching and out-of-plane wagging deformations originating from the nitric acid attack on the preformed char. , Thus, the FTIR analysis revealed that all CDs contain graphitic domains and surface functional groups, while NO 2 groups are introduced upon nitric acid treatment.…”
Section: Resultsmentioning
confidence: 85%
“…In addition, medium-intense peaks in CD 1 and CD 4 and more intense peaks in CD 2 and CD 3 are present at ∼1720 cm –1 due to carbonyl functional groups. A prominent peak corresponding to the −CC– bonds is observed in the 1620–1650 cm –1 region. ,,, In addition, in all samples, asymmetric and symmetric stretchings of −SO 3 groups are present at ∼1150 and ∼1017 cm –1 , respectively, originating from an H 2 SO 4 attack on the polymer backbone, and another peak at ∼860 cm –1 corresponds to the C–C ring and −CH 2 deformations. ,,, Notably, an additional peak (∼1265 and ∼730 cm –1 in CD 2 ) corresponds to the N–O stretching and out-of-plane wagging deformations originating from the nitric acid attack on the preformed char. , Thus, the FTIR analysis revealed that all CDs contain graphitic domains and surface functional groups, while NO 2 groups are introduced upon nitric acid treatment.…”
Section: Resultsmentioning
confidence: 85%